Deployment and Charging Station Plan for Public Electric Buses in Kathmandu Valley Using Linear Programming Method and Multi-Criteria Decision Analysis - Lamichhane, Madhu Sudan; Luintel, Mahesh Chandra; Adhikari, Surya (Journal of Innovations in Engineering Education, 2021)
The government of Nepal is planning to develop electric bus (e-bus) fleet in Kathmandu valley with an aim to reduce the city pollution. The SajhaYatayat, a governmental institution operating public buses in different routes of Kathmandu valley, is going to purchase e-bus for public services. The aim of this research is to develop models with which the number of buses can be minimized, and the best charging facility can be adopted by using Linear Programming and Multi-criteria Decision Analysis (MCDA) respectively. The six prominent routes of Sajha Yatayat were taken for models optimization. Many constraints affect the optimal number of buses that can be deployed in the routes. The data available from SajhaYatayat and the specification of the e-bus were the basic input parameters for linear programming model. The technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method was used to choose model charging facility among different models. The optimization results showed that the number of e-buses required is 40; each route consisting of 6 or 8 e-buses. These e-buses must be charged overnight in a central charging facility over terminal charging or opportunity charging. In this mode of charging facility the cost of operation can be minimal and the ease to maintain the fleet can be high. The result also showed that the lifetime cost of e-bus is 1.7 times lesser than that of diesel bus in terms of social and economic cost. The study presents that acquiring and deploying e-bus is financially and technically feasible.